Barriers to completion of maternal and neonatal continuum of care services in Assosa Zone, north-western Ethiopia - Solomon Abtew; Rose M. Mmusi-Phetoe (African Journal of Primary Health Care & Family Medicine)
Background: The continuum of care (CoC) in maternal and neonatal services among women in Ethiopia was low because of individual and cultural barriers.